ANALISIS PENGARUH INVESTASI SEKTOR TRANSPORTASI TERHADAP PERTUMBUHAN EKONOMI INDONESIA TAHUN 2004 - 2013 - TRI MULYANI SETYOWATI (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2015)
This research is conducted to find out how big is the role of foreign direct investment and domestic  for economic growth in Indonesia during the period 2004 – 2013 by using static model analysis with Ordinary Least Square regression. The result of the sectoral analysis  that  foreign direct investment and domestic transportation sector does not influence  the Indonesian economic growth .  It’s because of risk in country factor, that is small domestic  markets  that cause lower rate of return and lack of supporting facilities such as infrastructure and transportation, skilled employees, and technology.  Factor inhibiting the influx of investment also is a problem of economic  instability, political, security and legal certainty.The result of the multi sector analysis that  foreign direct  investment  and  domestic  for overall sectors  of the economy does influence the Indonesian  economic  growth with using a significance level of 10%.  Besides domestic  savingshas very strong influence to economic growth both for sectoral and multi sector analysis.